Literacy and Numeracy Skills of Primary School Students in the Wetland Environment of Banjarmasin City - Darmiyati, Darmiyati; Prihandoko, Yogi (Universitas Pahlawan Tuanku Tambusai, 2025)
Primary education is the foundation for the intellectual development of students, one of which can be measured through literacy and numeracy skills. However, in some areas, particularly in regions with specific environmental characteristics such as wetlands, there are numerous challenges that hinder the achievement of these basic competencies. This study aims to identify the factors influencing the low literacy and numeracy skills of elementary school students in schools located in the wetland areas of Banjarmasin City. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers and school principals, direct field observations, and literacy and numeracy tests to measure students' abilities. The findings show that the literacy and numeracy skills of students in the five schools are at a low level, caused by several factors, including limited educational facilities, low parental education levels, and the geographical and socio-economic challenges present in the wetland environment. Some recommendations for improvement include enhancing educational facilities, teacher training, and increasing parental involvement in supporting learning at home. This study provides insight into how environmental factors play a critical role in determining the quality of education in the area and offers solutions that can be implemented to address these issues